Sustainability Analysis of Pawn Products PT. Pegadaian (Persero) in the Competitive Climate of the Pawnshop Business - Jalaludin, Jalaludin; Eni Indriani; Isnawati, Isnawati; Ermawati, Ermawati (Socio-Economic and Humanistic Aspects for Township and Industry, 2023)
This research aims to empirically test the influence of pawnshop business competition on business sustainability. The population in this research is all customers of PT. Pegadaian (Persero) Aikmel Sub-Branch has 12,930 customers. The number of samples used was 400 customers which was determined based on a simple random sampling technique. The analysis technique used is Structural Equation Modeling-Partial Least Square (SEM-PLS). The research results show that pawn business competition has a positive effect on the sustainability of PT's pawn products. Pegadaian (Persero). It is hoped that the implications of this research can be used as consideration by PT. Pegadaian (Persero) in responding to the ongoing business competition and also this research can be used as a benchmark to see the public's response regarding the comparison between PT. Pegadaian (Persero) with other pawnshop companies.